Perkembangan Anak Disabilitas (Anak Tunarungu Belajar Melalui Metode Oral) - Siti Wahyuni (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2018)
Oral method is one way to train deaf children to be able to communicate orally (verbally) with neighborhood who heard that deaf children are required to speak demanded their participation of the people around them, involving deaf children to speak orally in every in every chance. By giving a chance to talk to them, get it implies that deaf children are motivated to get used to speak verbally deaf children get difficulties in developing spoken language because of lack or do not hear the sounds of the language, because of hearing function is not maximized, whereas deaf children generally still have residual hearing. To overcome these difficulties oral method suitable to be used.